(untitled) (International Journal of Petroleum Technology, 2015)
The addition of water dispersed phase into the diesel continuous phase will lead to the formation of water-in-diesel (W/D) emulsion, which significantly reduces the pollution level of NOx and particulate matters in the diesel engines. Small amount, 0.2% by volume, of surfactant material was necessary in the preparation of a stable W/D emulsion. The study of the physical and chemical properties of stable W/D emulsions is important to understand the flow behavior characteristics of these emulsions. Pure diesel fuel and three samples of W/D emulsions (10%, 20% and 30% by volume water) were examined in this study. The following properties are measured according to the corresponding ASTM standards for the pure diesel and its emulsions with 10%, 20% and 30% water: heating value, pour point, flash point, distillation data, density, viscosity, calculated cetane index, total acid number, and sulfur content. The addition of water in the emulsion caused a drop in the calorific value, final boiling point, cetane index, total acid number, and sulfur content. Increasing the water also increased the pour point, flash point, and density.